RETHINKING FINANCIAL DISTRESS DETERMINANTS: INSIGHTS FROM THE AGRO-INDUSTRIAL SECTOR - Čavlin , Miroslav; Vapa-Tankosić, Jelena; Dmitrović, Veljko; Suljić Nikolaj, Stella; Mikerević, Dejan (Economics of Agriculture, 2026)
This paper examines the determinants of financialdistress in the agro-industrial sector of the Republicof Serbia. The empirical analysis is based on paneldata for 20 large companies from the food productionsector in the period 2019–2024. Financial distress wasoperationalized using the revised Altman Z′ indicator,with an extended classification threshold (Z′ < 1.8). Binarylogistic regression was applied to assess the impact ofselected variables. The findings have shown that thecapital structure is the dominant determinant of financialdistress, while indicators of profitability and operatingcash flows do not show a statistically significant influence.At the same time, company size stood out as a significantfactor, with larger companies more likely to face financialdifficulties. The findings indicate that financial distressis not primarily conditioned by operational performance,but primarily by the structural characteristics of financingindicating the need for the development of integrative andmultidimensional analytical approaches in this area.